Biosilo de residuos de merluza y harina de cebada fermentados con bacterias ácido láctica - Marguet, Emilio Rogelio (2017)
Suitability of Lactococcus lactis Tw34 and Lactobacillus plantarum Lb7 asbio-silage inoculants was studied. Experiments were carried out with a mixtureof hake (Merluccius hubbsi) by-products and barley meal fermentedduring 7 days. A sample acidified with lactic acid was used as control. Inbiological mixtures, the pH dropped below 5,0 after 2 days of fermentationand remained stable until the end of the experience. Maximum populations(> 109 CFU/g) were reached after 5 days of incubation at 18°C. Water solublepeptides concentration increased during the 7 days of incubation andno significant differences (p < 0,05) were found between the control andboth bio-silage. Trichloroacetic acid soluble peptides concentrations of biosilageswere higher than the control (p > 0,05). After 7 days, phosphorousconcentrations reached 2.26 and 2,42 g/100 g in bio-silages fermented withLc. lactis Tw34 and Lb. plantarum Lb7, respectively, while control values remainsalmost stable (1,61 g/100 g). At the end of the experience, inhibitoryactivity of trypsin was abolished in both bio-silage while in control sampleantinutritional factors remained active. The results indicated the feasibility ofthe use of the selected mixture as substrate for bio-silage production andthe effectiveness Lc. lactis Tw34 and Lb. plantarum Lb7 as inoculants.